Obecność salezjanów na Wołyniu - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2011)
Wanda Mamertyna Jasieńska from Tudorów (poviat Równe in Volhynia) died of cancer 22 January 1935 in Warsaw. Three months before her death she bequeathed her landed estate of over 200 hectares in Tudorów to the Salesians of St Jacek Province, whose provincial superior was the Rev. Tomasz Kopa. In return, the Salesians were supposed to organise an educational institution which could run gardening courses for young people. Wanda lived with her mother in Żytomierz. When she was 16 - in 1886, she married Władysław Konstanty Wincenty Jasieński, the landowner from Tudorów, whose land estate she inherited after his death and after paying off the incurred debts. They had no children. After the death of her mother Alina in 1914 in Żytomierz, Wanda did not divide her mother’s inheritance to give one part of it to her sister Wieńczysława Regina, who repeatedly claimed her part of the property. At that time Józef Bronikowski from Równe started visiting Wanda. He became her and her husband’s confidant. In 1926 Wanda endowed his family with a land of about 20 hectares along with a house and outbuildings, and when her husband Władysław died in 1929, Bronikowski took control of Wanda’s landed estate in Tudorów. During Wanda’s incurable disease, Bronikowski isolated her on purpose and he not only managed the property, but also decided about Wanda’s treatment excluding her family or anybody whom she knew. Finally, a few months before she died, he influenced sick Wanda, whose sanity was doubtful, to make a will. According to Wanda’s family, Bronikowski terrorised the sick woman in the last months of her life. He did not let anyone visit her and he controlled her private correspondence for his own purposes. The departed Wanda Jesieńska was buried in her land in Tudorów, where according to her wish, a chapel for Salesian pastoral work was to have been built. The Salesians could take over the land that was given to them by Wanda only after the death of the land agent, Józef Bronikowski, who was to manage it at his own discretion without any intervention from both the family and the Salesians who were inheritors. He was not even obliged to submit any reports and accounts of the property management It is interesting that the departed Wanda did not bequeath anything to her only sister, Wieńczysława. She made a small bequest to her sister’s children, servants in the manor house, charitable purposes and the National Museum in Krakow. A privileged position of Bronikowski and humiliating position of the inheritors who did not have the right to make use of the property bequeathed to them during Bronikowski’s life indicates that the will was made to bring advantages to Bronikowski whose property management made a substantial contribution to his income. When Wanda’s will became legally binding, the family took measures to invalidate it. The case was first examined in Równem, then in the Court Appeal in Lublin and finally in the Supreme Court in Warsaw. The Salesians in the person of provincial superior from Krakow, who were endowed with a doubtful bequest, did not support the family’s endeavours. The Second World War prevented Wanda’s family from pursuing further claims concerning the inheritance. Also, Brokikowski was deprived of the right to the property income when Volhynia became a part of the Soviet Union after the Second World War.